Optimal Jamming Attack Scheduling in Networked Sensing and Control Systems. (8th October 2015) - Zhang, Lifu; Zhang, Heng; Li, Cunhua; Ni, Buxi
Abstract : This paper investigates the optimal jamming attack scheduling in Networked Sensing and Control Systems (NSCS). From viewpoint of the attacker, we formulate an optimization problem which maximizes the Linear Quadratic Gaussian (LQG) control cost with attacking energy constraint in a finite time horizon. For two special cases, we obtain that the optimal jamming attack schedule is to consecutively attack in the given time horizon. For the general case, we propose an algorithm to find the optimal schedules. Finally, we study the effectiveness of our proposed attack strategies on our established semiphysical testbed.